2014
DOI: 10.1097/brs.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Perfusion Characteristics of Hypervascular Renal and Hypovascular Prostate Spinal Metastases

Abstract: Study Design Total of 40 patients with spinal metastases from renal cell carcinomas (RCC) or prostate carcinomas (PC) were studied using DCE (Dynamic contrast-enhanced) MRI. Objective Our aim was to evaluate spinal metastases from RCC and PC to assess the sensitivity and specificity of perfusion parameters obtained by quantitative and semi-quantitative methods, which would allow for noninvasive discrimination between hypovascular and hypervascular lesions. Summary of Background Data Conventional MRI can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…These quantitative parameters have demonstrated their value in detecting the differences in microvascular environment among metastatic lesions before and after treatment 9 , benign and pathological fractures 10 , and hypovascular and hypervascular lesions. 11,12 Vertebral metastases demonstrate very different histological patterns depending on the primary tumor. There is, however, a common feature in all of them: neoangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These quantitative parameters have demonstrated their value in detecting the differences in microvascular environment among metastatic lesions before and after treatment 9 , benign and pathological fractures 10 , and hypovascular and hypervascular lesions. 11,12 Vertebral metastases demonstrate very different histological patterns depending on the primary tumor. There is, however, a common feature in all of them: neoangiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the analysis methods, most studies found DCE parameters showing significant differences between diseased and normal bone marrow, or between different lesions(815). Khadem et al used heuristic DCE analysis to discriminate hypervascular from hypovascular spinal metastases (12), and later Saha et al from the same research group showed that pharmacokinetic parameters analyzed by using a commercial software (NordicNeuroLab) could distinguish hypervascular renal cell carcinoma from hypovascular prostate carcinoma (13). DCEMRI using heuristic analysis and model fitting has been applied to characterize vascular properties of different hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement (8,9,15).…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI has been applied to diagnose different spinal lesions (811) and distinguish between hypervascular (eg, renal cell carcinoma) and hypovascular (eg, prostate cancer) metastases (12,13). It has also been used to characterize vascular properties of hematologic malignancies (eg, myeloma and lymphoma) with different grades of bone marrow involvement, as well as to evaluate changes after various therapies for predicting treatment outcome and prognosis (8,9,1420).…”
Section: Introductionmentioning
confidence: 99%
“…DCE-MRI involves assessing changes in signal intensity over time: before and after contrast injection (12). Previous studies have shown that DCE-MRI is useful for monitoring response to therapy in spinal bone metastases (13), and for discriminating between the hypo- and hyper- vascular spinal lesions of prostate carcinoma and renal cell carcinoma, respectively (14). More recently, DCE-MRI has shown clinical utility in chordoma diagnosis, effectively discriminating between chordoma and giant cell tumors of the axial skeleton (15).…”
Section: Introductionmentioning
confidence: 99%